2020
DOI: 10.1088/1361-6528/abcd60
|View full text |Cite
|
Sign up to set email alerts
|

Optical design of InGaN/GaN nanoLED arrays on a chip: toward: highly resolved illumination

Abstract: The physical laws of diffraction limit the spatial resolution of optical systems. In contrary to most superresolution microscopy approaches used today, in our novel idea we are aiming to overcome this limit by developing a spatially resolved illumination source based on semiconductor nanoscale Light Emitting Diode (nanoLED) arrays with individual pixel control. We present and discuss the results of optical simulations performed for such nanoLED emitter arrays and analyze the theoretical limits of this approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…In this work, the points sources are placed at the center of the 3 × 3 lattice ( Figure S2b ). The effect of the relative locations of the sources is negligible in a 3 μm × 3 μm LED source, as the 3 × 3 array of dipole sources provides a similar light emission to a single point source of the same size [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this work, the points sources are placed at the center of the 3 × 3 lattice ( Figure S2b ). The effect of the relative locations of the sources is negligible in a 3 μm × 3 μm LED source, as the 3 × 3 array of dipole sources provides a similar light emission to a single point source of the same size [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extracted resolution from one of the 1.6 µm square’s edges was 1.56 µm ( Figure 10 b), four times the expected resolution (400 nm), since the sample was placed directly over the nanoLEDs. However, further analysis of the nanoLED array configuration (by finite difference time domain simulations [ 26 ]) showed that the metal structure and the depth of the light emitter region affected the spot shape and size at the chip surface, degrading the resolving power of the setup.…”
Section: Resultsmentioning
confidence: 99%
“…Efficient and ecological small photon emitters, e.g. nano/micro-scale light emitting diode (LED) [1][2][3][4][5][6] and monolithic RGB emitters [7][8][9] , are required for next generation lighting and display applications. Reliable single photon sources (SPS or single photon emitter: SPE) 10 , which provide on-demand single photons are indispensable in the field of rapidly growing quantum technologies such as quantum computing, quantum sensing, and quantum communications (quantum internet) [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%